Journal of Fourier Analysis and Applications - Feichtinger, Hans G.; SpringerLink (Online service) (New York : Springer US : Imprint: Birkhäuser.)
The Journal of Fourier Analysis and Applications will publish results in Fourier analysis, as well as applicable mathematics having a significant Fourier analytic component. Appropriate manuscripts at the highest research level will be accepted for publication. Because of the extensive, intricate, and fundamental relationship between Fourier analysis and so many other subjects, selected and readable surveys will also be published. These surveys will include historical articles, research tutorials, and expositions of specific topics. The Journal of Fourier Analysis and Applications will provide a perspective and means for centralizing and disseminating new information from the vantage point of Fourier analysis. The breadth of Fourier analysis and diversity of its applicability require that each paper should contain a clear and motivated introduction, which is accessible to all of our readers. Areas of applications include the following: antenna theory * crystallography * fast algorithms * Gabor theory and applications * image processing * number theory * optics * partial differential equations * prediction theory * radar applications * sampling theory * spectral estimation * speech processing * stochastic processes * time-frequency analysis * time series * tomography * turbulence * uncertainty principles * wavelet theory and applications Bibliographic Data First published in 1994 1 volume per year, 6 issues per volume Format: 17 x 24 cm ISSN 1069-5869 (print) ISSN 1531-5851 (electronic) AMS Mathematical Citation Quotient (MCQ): 0.92 (2018).
Keywords: Harmonic analysis; Approximation theory; Fourier analysis; Partial differential equations; Physics; Signal processing; Image processing; Speech processing systems; Fourier Analysis; Signal,Image and Speech Processing; Abstract Harmonic Analysis; Approximations and Expansions; Partial Differential Equations; Mathematical Methods in Physics